Homesick : a memoir - Croft, Jennifer (Translator) (The Unnamed Press, 2019)
"The coming of age story of an award-winning translator, HOMESICK is about learning to love language in its many forms, healing through words and the promises and perils of empathy and sisterhood. Sisters Amy and Zoe grow up in Oklahoma where they are homeschooled for an unexpected reason: Zoe suffers from debilitating and mysterious seizures, spending her childhood in hospitals as she undergoes surgeries. Meanwhile, Amy flourishes intellectually, showing an innate ability to glean a world beyond the troubles in her home life, exploring that world through languages first. Amy's first love appears in the form of her Russian tutor Sasha, but when she enters university at the age of 15 her life changes drastically and with tragic results."--provided by publisher.